Sexploitation and Non-marital Sex Normalization Discourse in USS Feed - Muhammad Dicka Ma'arief Alyatalatthaf; Heppy New Year Haloho (Departemen Ilmu Komunikasi FISIP Universitas Atma Jaya Yogyakarta, 2024)
Some Indonesian media outlets that produce sex education videos exploit sexuality to attract viewers instead. This research aims to identify the sexual commodification and non-marital sex normalization in